A surface ocean trajectories visualization tool and its initial application to the Galician coast. (April 2015) - Otero, P.; Banas, N.S.; Ruiz-Villarreal, M.
Abstract: Alavai is a free tool built with Processing to visualize forecasts of drift trajectories in the sea in a very fast and user-friendly graphic environment. It plots trajectories of both passive particles trapped near the ocean surface and oil slicks. Input data come from an operational configuration of the ROMS ocean model focused on the Euroregion Galicia (Spain) – North Portugal, however, this tool is easily adaptable to run with outputs coming from any operational high resolution ocean model configuration. The Prestige accident is used here in hindcast mode to demonstrate the main characteristics of Alavai. Graphical abstract: Highlights: A free, fast and friendly tool to visualize ocean surface drift is disseminated. It is easily adaptable to any high resolution ocean model configuration. 3-days forecast oil spill and passive surface particles trajectories are plotted. The usefulness is demonstrated in hindcast mode during the Prestige accident.